AN UNUSUAL PRESENTATION OF TYPE I KOUNIS SYNDROME: HIGH TROPONIN WITHOUT CHEST PAIN AFTER ANAPHYLAXIS - Čekić, Said; Gutić, Medo; Milidrag, Ardea (Sanamed, 2025)
Introduction: Kounis syndrome is defined as the simultaneous occurrence of acute coronary syndrome and an allergic or anaphylactic reaction. It primarily affects men between 40 and 70 years of age and is often associated with chest pain. Owing to limited awareness, this syndrome is frequently under-recognized and under-diagnosed in clinical practice. Case presentation: We report a case of type I Kounis syndrome in a young woman without chest pain. The patient, who had allergic asthma since childhood, developed anaphylactic shock during the administration of bronchodilators, corticosteroids, and an antibiotic in an emergency outpatient setting, followed by cardiac arrest. Subsequent laboratory testing confirmed acute coronary syndrome. Conclusion: Although Kounis syndrome is uncommon, particularly in young women, clinicians should consider the possibility of acute coronary syndrome in severe allergic reactions. In this case, myocardial injury was documented by electrocardiographic changes and later by cardiac biomarkers consistent with coronary syndrome.